Biscuits, Baking & Cakes : The Essential Recipe Handbook - Edited by Steer, Gina (London Flame Tree Publishing, 2008)
Beginning with a useful section on equipment and basic techniques, this guide then includes dishes such as Fish Puff Tart and Chicken & Ham Pie to ensure there is a good choice of savoury recipes to complement the sweet. It also features all kinds of everyday cakes and biscuits before ending on a high of celebration cakes and gateaux
Include Colour Illustrations
Keywords: Baking -- Baked products